2021
DOI: 10.1136/bmjopen-2020-044319
|View full text |Cite
|
Sign up to set email alerts
|

Statin therapy for patients with aortic stenosis who underwent transcatheter aortic valve implantation: a report from a Japanese multicentre registry

Abstract: ObjectiveData on statin for patients with aortic stenosis (AS) who underwent transcatheter aortic valve implantation (TAVI) are limited. The present study aimed to evaluate the impact of statin on midterm mortality of TAVI patients.DesignObservational study.SettingThis study included patients with AS from a Japanese multicentre registry who underwent TAVI.ParticipantsThe overall cohort included 2588 patients (84.4±5.2 years); majority were women (69.3%). The Society of Thoracic Surgeons risk score was 6.55% (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The leave-one-out analysis showed the studies by Yashima et al 9 and Cubeddo et al 17 to be influential studies. The result of pooled analysis with the influential studies removed, also showed that statins therapy is associated with lower risk of all-cause mortality (HR = .76, 95% CI 0.64–.90, P = .0014; I 2 = 37.7%, Q value = 22.47, P = .0695).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The leave-one-out analysis showed the studies by Yashima et al 9 and Cubeddo et al 17 to be influential studies. The result of pooled analysis with the influential studies removed, also showed that statins therapy is associated with lower risk of all-cause mortality (HR = .76, 95% CI 0.64–.90, P = .0014; I 2 = 37.7%, Q value = 22.47, P = .0695).…”
Section: Resultsmentioning
confidence: 98%
“…The flow chart presenting the selection of the articles is shown in (Figure 1). Of included studies, 6 studies reported adjusted HR, 9,10,16,17,19,21 6 studies reported unadjusted HR 11,15,18,23,25,26 and, RRs were calculated for 5 studies. 20,22,24,27,28 The follow-up duration ranged from 12 to 60 months.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 665 citations were identified, and 210 potentially eligible articles were retrieved in full text. Overall, 54 studies were included in the review ( Figure 1 ) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Risk of bias assessment using NOS showed that the studies have low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…However, meta-analyses of observational studies and sub-studies of randomized trials have shown significant associations between statin treatment and better long-term survival in TAVI patients. 14 , 15 , 25 The mechanism is unclear, but it has been speculated that statin therapy reduces the risks of mortality through a reduction of ischaemic events. 25 The results of studies in TAVI populations cannot be directly translated to SAVR patients given that most TAVI patients are markedly older and have more comorbidities than SAVR patients.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 , 25 The mechanism is unclear, but it has been speculated that statin therapy reduces the risks of mortality through a reduction of ischaemic events. 25 The results of studies in TAVI populations cannot be directly translated to SAVR patients given that most TAVI patients are markedly older and have more comorbidities than SAVR patients. In this study, 27.5% of the patients had a diagnosis of hyperlipidaemia and 49.1% were treated with statins at baseline, indicating that a substantial number of patients were prescribed statins because of risk factors and comorbidities other than hyperlipidaemia.…”
Section: Discussionmentioning
confidence: 99%